A Few Reflections on Suicide and Profane Death from not only an Archaeological Perspective on the Margins of Paweł Duma’s Book, ‘Profane Death in Burial Practices of a Pre-Industrial Society. A Study from Silesia’. - Kalina Skóra (Fasciculi Archaeologiae Historicae)
A Few Reflections on Suicide and Profane Death from not only an Archaeological Perspective on the Margins of Paweł Duma’s Book, ‘Profane Death in Burial Practices of a Pre-Industrial Society. A Study from Silesia.